EFEKTIVITAS EKSTRAK TEH HIJAU (Camellia sinensis L.) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL TIKUS WISTAR (Rattus norvegicus) DIABETES YANG DIINDUKSI ALOKSAN - Zufarisky Sarel (2020)
Green Tea (Camellia sinensis L.) contains flavonoid compounds, works as an anti-dyslipidemia due to chronic hyperglycemia of diabetes. This study aims to determine the effectiveness of green tea extracts on reducing total cholesterol levels in alloxan-induced Wistar diabetic rats. The design of this study is true experimental. Samples were 30 male white Wistar rats, aged 8-12 weeks, weighing ± 200 g. Green tea extract doses of 200, 400, and 800 mg / kg body weight, and negative controls were given alloxan, and positive controls were given simvastatin. The treatment group except the normal group was injected with a dose of 125 mg / kg alloxan intraperitoneally and high-fat feed. After 3 days blood from the tail was measured glucose using a glucometer and cholesterol with a spectrophotometer λ = 546 nm, giving green tea extract for 16 days orally, then re-measuring blood cholesterol from the tail. The paired T test results showed there was a decrease in total cholesterol levels after treatment (p = 0,000). One Way Anova test showed that there was an effectiveness of green tea extract to reduce total cholesterol level (p=0,000). Post-Hoc Bonferroni test results exhibited giving green tea extract a dose of 400 mg / kg comparable to simvastatin (p=0.453) that best for reduce total cholesterol levels close to normal values.